Flexible nickel foam decorated with Pt/NiO nanoflakes with oxygen vacancies for enhanced catalytic formaldehyde oxidation at room temperature. Issue 11 (5th October 2017) - Huang, Shuying; Zhu, Xiaofeng; Cheng, Bei; Yu, Jiaguo; Jiang, Chuanjia
Abstract : Flexible nickel foam coated with Pt/NiO nanoflakes was prepared for HCHO catalytic oxidation at ambient temperature. Abstract : Catalytic formaldehyde (HCHO) oxidation at ambient temperature is an efficient technology for indoor air purification. Herein, flexible nickel (Ni) foam coated with Pt/NiO nanoflake catalysts was prepared through fast chemical bath deposition, which exhibited enhanced activity for HCHO removal at room temperature. In contrast, no HCHO oxidation activity was observed for the control samples without loading platinum (Pt) or coating nickel(ii ) oxide (NiO) nanoflakes. By optimizing the deposition duration, an almost 90% HCHO removal efficiency was achieved within 1 h over the sample with 1 h deposition time. The deposition of NiO nanoflakes over Ni foam not only forms a hierarchical structure facilitating the reactions kinetically, but also provides sufficient oxygen vacancies promoting Pt deposition and consequent HCHO oxidation. The HCHO oxidation activity of the catalysts positively correlated with the Pt dispersion and with the proportion of oxygen-deficient NiO, as determined by hydrogen temperature programmed reduction. Moreover, the mechanism of room-temperature HCHO catalytic oxidation over the as-prepared catalysts was investigated by in situ diffuse reflectance infrared Fourier transform spectroscopy, which identified formate and dioxymethylene as the main reaction intermediates. Compared with powder-like catalysts, the Ni foam-supported Pt/NiO catalysts have great flexibility and machinability, holding great promise for actual application.